The impact of using the Alef platform on 11th grade advanced mathematics students' achievement in conic sections - Anas Mahmoud Ahmad Alrababah; Eric Machisi (Universitas Sarjanawiyata Tamansiswa, 2025)
This study investigates the impact of the Alef educational platform on student learning outcomes in the topic of conic sections, focusing on both academic performance and student perceptions. The research involved a purposive sample of 64 Grade 11 advanced mathematics students from a high school in Fujairah, United Arab Emirates. A quasi-experimental design was employed, incorporating pre-test and post-test assessments. Data were collected through a researcher-developed test and an online Likert-scale survey. The findings indicate that the Alef platform significantly enhances students’ understanding of conic sections by personalizing instruction to meet individual needs and by using interactive media to present multiple representations of mathematical concepts. This approach caters to diverse learning styles and promotes deeper engagement. Moreover, students reported being able to recall key lesson ideas effectively and felt comfortable participating in class without fear of ridicule. They expressed enjoyment in learning conic sections through the Alef platform and expressed a desire for its broader integration across mathematics lessons. Overall, the Alef platform positively influenced students’ perceptions of mathematics. The study highlights the value of integrating technology into mathematics education to create a more inclusive and effective learning environment. This study contributes to mathematics education by providing empirical support for the use of technology-enhanced, student-centered learning environments—grounded in constructivist and self-determination theories—to improve conceptual understanding and motivation in specific mathematical topics.